A TEXTBOOK EVALUATION OF ENGLISH LISTENING MATERIALS FOR THE TENTH GRADE BASED ON THE 2013 CURRICULUM - RISWANTO, RISWANTO; ROMANIA, YOSI OKTA; MARTINA, FENY (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
The purpose of this research is to determine whether or not the listening materials included in the English textbooks used by students in the tenth grade at SMAN 04 Bengkulu City match the requirements outlined in the curriculum that was implemented in 2013. This research is extremely important to the academic world since it will make it much easier for both students and teachers to select a good textbook. A content analysis was utilized in the current investigation. During the data collection process, the researchers utilized two different analysis matrices. The first matrix of analysis consisted of making connections between the listening materials in the textbook and the academic program for 2013. The second analysis matrix presents the percentage score that the English textbook was given in accordance with the standards of the 2013 curriculum. The first matrix illustrates, in accordance with the conclusions of the analysis of the data, that the listening materials contained within the English textbook is compatible with the curricular plan for 2013. In the second matrix, English textbooks are categorized as